SELF DISCLOSURE PADA MEDIA SOSIAL(Studi Deskriptif Pada Media Sosial Anonim Chatous) - Sujiwo Duta Kusuma (2022)
Self disclosure on anonymous social media tend to be utopist, where the users don't know each other but still doing self disclosure, generally the factors of a person doing self disclosure is because they know each other. Self disclosure on Chatous occurs because of the need to self disclosure about various things that sometimes cannot be discussed on non-anonymous social media. The purpose of this research are to know how Chatous user doing their self disclosure on the Chatous platform. This research use self disclosure theory (Johari Window). This research use qualitative approach with descriptive method. The type of the research that were used are fenomenology. The data were collected through interview, observation, and documentation. There is five informants on this research, found through purposive sampling. The results of this research shows that doing self disclosure on anonymous social media Chatous made the users more comfortable and feels safe for them to open up about themselves. The dimension or measurements about the frequency and duration aspects in the case of self disclosure from the informants were very erratic an unpredictable. The function of self disclosure that occurs in social media Chatous such as, have a function as a form of expression. Factors such as the amount of people on the group affecting the willingness of a person to open up in Chatous. The negative effects of self disclosure from theory did not found on Chatous.